2018
DOI: 10.1371/journal.pone.0205995
|View full text |Cite
|
Sign up to set email alerts
|

Two novel temperate bacteriophages infecting Streptococcus pyogenes: Their genomes, morphology and stability

Abstract: Only 3% of phage genomes in NCBI nucleotide database represent phages that are active against Streptococcus sp. With the aim to increase general awareness of phage diversity, we isolated two bacteriophages, Str01 and Str03, active against health-threatening Group A Streptococcus (GAS). Both phages are members of the Siphoviridae, but their analysis revealed that Str01 and Str03 do not belong to any known genus. We identified their structural proteins based on LC–ESI29 MS/MS and list their basic thermal stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Bacteriophages from groups D and G were relative to S. agalactiae phages LF2 and LF4 [ 20 ]. Group E bacteriophages were similar to S. agalactiae phage LF3 [ 20 ] and S. pyogenes phage Str03 [ 43 ] ( Figure 2 A; Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteriophages from groups D and G were relative to S. agalactiae phages LF2 and LF4 [ 20 ]. Group E bacteriophages were similar to S. agalactiae phage LF3 [ 20 ] and S. pyogenes phage Str03 [ 43 ] ( Figure 2 A; Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…2a . At the right of the end of prophage, there is a CDS encoding enolase (depicted as a green arrow), which is a surface-exposed adhesion protein of Streptococcus suggested to be a phage receptor or to interact with proteins of phages 33 . The aligned viral sequence in the IMG/VR v2.0 database encoded 14 CDSs, but its taxonomic classification using CAT was impossible.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteriophage Pf4, which has as a host Pseudomonas aeruginosa strain PAO1, was able to be converted into a superinfective form, producing plaques on its host’s bacterial lawn circumventing Pf4-mediated immunity (Rice et al, 2009). More recently it was reported that bacteriophages Str01 and Str03 were spontaneously released from Streptococcus pyogenes PCM 2855 and that very strain was subsequently used as their host for propagation (Harhala et al, 2018). In this case the authors examined whether the phages were prophages from the host bacteria but could not confirm their presence in the bacterial genome either by PCR or following whole genome sequencing of the host, suggesting that these were more likely environmental viruses that contaminated the original sample.…”
Section: Resultsmentioning
confidence: 99%